(untitled) (Research, Society and Development, 2018)
The article integrates the studies carried out as part of a concluded research which aimed to analyze the intergovernmental relations established by the federated entities in the implementation of policies created in the framework of the Federal and State Governments oriented towards the ongoing development of literacy teachers and the role played by the municipalities in the execution of such policies in the period between 2003 and 2006. As an integral part of the broad analysis, this text discusses the policy and management of the ongoing development of teachers in Brazil, considering the federative coordination and collaboration between 2003 and 2006. It presents an analysis carried out in documents of the National Policy of Recognition and Development of Teachers, redesigned in the beginning of 2003, especially the National Network of Ongoing Development of Basic Education Teachers. It also emphasizes the guidelines agreed upon set down to initiate collaborative efforts between the federated entities and universities to implement this policy. The examination reveals signs of a centralized federal formulation and a decentralized offer, and indicates different reactions by states and municipalities to the model of federalism adopted in the policies, giving rise to contradictions in the structure of roles played by the subnational units.